Comparison of Continuous Femoral Nerve Block versus Local Infiltration Analgesia as a Postoperative Analgesia in Unilateral Total Knee Arthroplasty - Chaubey, Deepika (J Clin Diagn Res, 2017)
INTRODUCTION: Local infiltration of knee joint in arthroplasty, provide postoperative analgesia and preserves motor power of quadriceps, which helps in early mobilisation, as compared to femoral nerve block which paralyses vastus medialis. AIM: To compare the quality of postoperative analgesia provided by femoral nerve block and local infiltration in unilateral Total Knee Arthroplasty (TKA). MATERIALS AND METHODS: A prospective study was conducted on 60 patients (25-65 years) of ASA I and II, which were randomly(using random number table) divided into two groups – Group 1-femoral nerve block (FNB) and Group 2-Local Infiltration Analgesia (LIA). Patients with chronic pain and on opioids were excluded. Numeric rating scale (primary objective), sedation score, nausea vomiting score and motor power were analysed. The results were analysed by parametric and nonparametric tests using SPSS software version 22. p<0.05 was considered significant. RESULTS: Pain relief was better in FNB Group (p-value <0.001) with less fentanyl demand (p-value <0.001), low sedation score (0.013, 0.179, 0.018, 0.129, 0.287, 0.432) but associated with low muscle power grading (<0.001). CONCLUSION: FNB has better pain relief than LIA Group but range of motion was reduced in FNB Group grossly, effect on mobilisation remained comparable in both group.